Textile Finds from the Early Medieval Cemetery in Glinno, Sieradz District. New Data for the Research on Textile Production in Central Poland - Łukasz Antosik; Tomasz Kurasiński (Fasciculi Archaeologiae Historicae)
The present paper is devoted to a detailed discussion of a set of textile remains (5 fragments) from the inhumation cemetery in Glinno, Site 15, Sieradz District, Łódzkie Voivodeship (mid-11th – mid-12th century). They were discovered in Graves 1-2 and 18. All discussed textile remains were found to be in a poor state of preservation. Despite that, the analysis revealed that these were local products characteristic for domestic production whose quality does not differ from other products from Central Poland. Their function is not clear; however, the textile fragments from the inside of a knife sheath and the knife possibly indicate technical textile (lining). In the case of other textile finds, a funeral function should be generally presumed, considering a high probability that the objects were wrapped in a piece of cloth.